Study of density, abundance and distribution of (Gmelina arborea Roxb.) in Kengkhar, Monggar, Bhutan - Thukten Dorji (CNR, Lobesa Thukten Dorji, 2022)
includes acknowledgement and abstract
Keywords: Thesis